Early breastfeeding initiation and incidence of severe neonatal jaundice in Chipinge district Zimbabwe - Mugadza, Gladys; Zvinavashe, Mathilda; Gumbo, Zvanyadza; Stray-Pedersen, Babill (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal jaundice is the most prevalent condition affecting new born babies especially during the first week of life. About 50-60 % of the new born babies get affected with jaundice in the first week of life. The objective of the present study is to determine early breastfeeding initiation (EBFI) and the incidence of severe neonatal jaundice in in the first week of life in Chipinge District, Zimbabwe. Methods: A prospective cohort was conducted among 200 (100 early initiators and 100 late initiators) healthy term neonates and screening of jaundice was done on day 3 and day 7 using the transcutaneous bilirubinometry (JM 120). Early breast-feeding initiation was defined as the actual giving of the first breastmilk within an hour of birth and anything beyond an hour was considered as late (WHO, 2010). Jaundice was graded from mild (<10mg/dl), moderate (>10<14mg/dl) to severe (15mg/dl or more). Results: The Pearson correlation for early breastfeeding and severe neonatal jaundice was significant 2 tailed at (P = 0.01) at 95% CI and significant 2 tailed (P = 0.01) at 95% CI delayed breastfeeding initiation and severe neonatal jaundice. Conclusions: Early breast-feeding initiation had strong association with severe jaundice, significant 2 tailed at (P = 0.01) at 95% CI and significant 2 tailed (P = 0.01) at 95% CI delayed breastfeeding initiation and severe neonatal jaundice. There is need to assess neonatal jaundice objectively as clinical assessment through eye observation has limitation in picking at risk babies.